Study on the Role of FNAC in the Diagnosis of Head and Neck Lesion from Garhwal Region, Uttarakhand, India - Arvind Kumar; Sheela Choudhary; Deepa Hatwal; Neha Batra; S. K. Barpanda (New Frontiers in Medicine and Medical Research Vol. 3, 2021)
Background and Objectives: The present study was intended to study the spectrum of disease by aspiration cytology as well as evaluating its diagnostic utility in palpable head and neck lesion of Garhwal population in Uttarakhand. Materials and Methods: Retrospective study conducted on 796 patients presented with palpable head and neck mass. FNAC procedure was done using 23-24 G needle. Smears were stained by Giemsa and Pap smear and special stains. Results and Conclusion: Most common clinical presentation was cervical lymphadenopathy 67.8% and lesion was reactive lymphoid hyperplasia 33.3%. Metastatic carcinoma in cervical lymph node 58.57% was noted in majority of patient suffering from malignancy. FNAC proved to be fast, cost effective and reliable procedure for prompt diagnosis.